Biomaterials for Three-Dimensional Cell Culture: From Applications in Oncology to Nanotechnology - Tarek Saydé; Omar El Hamoui; Bruno Alies; Karen Gaudin; Gaëtane Lespes; Serge Battu (Nanomaterials, 2021)
Three-dimensional cell culture has revolutionized cellular biology research and opened the door to novel discoveries in terms of cellular behavior and response to microenvironment stimuli. Different types of 3D culture exist today, including hydrogel scaffold-based models, which possess a complex structure mimicking the extracellular matrix. These hydrogels can be made of polymers (natural or synthetic) or low-molecular weight gelators that, via the supramolecular assembly of molecules, allow the production of a reproducible hydrogel with tunable mechanical properties. When cancer cells are grown in this type of hydrogel, they develop into multicellular tumor spheroids (MCTS). Three-dimensional (3D) cancer culture combined with a complex microenvironment that consists of a platform to study tumor development and also to assess the toxicity of physico-chemical entities such as ions, molecules or particles. With the emergence of nanoparticles of different origins and natures, implementing a reproducible in vitro model that consists of a bio-indicator for nano-toxicity assays is inevitable. However, the maneuver process of such a bio-indicator requires the implementation of a repeatable system that undergoes an exhaustive follow-up. Hence, the biggest challenge in this matter is the reproducibility of the MCTS and the associated full-scale characterization of this system’s components.